Experimental and numerical investigations of the electro-viscoelastic behavior of VHB 4905TM - Mehnert, Markus; Mokarram, Hossain; Steinmann, Paul (European Journal of Mechanics A-Solids, 2019)
Dielectric elastomers are a class of electro-active polymers (EAPs) that can be used for the development of simple soft actuators, sensors and energy harvesters. Their operation principle is based on the interaction of quasi-static electric charges in combination with soft dielectrics and deformable electrodes. Due to their ability to undergo large deformations with a time dependent material response of the underlying polymer, the mechanical behaviors of EAPs can be described by a finite strain viscoelastic material model [1]. This model is here augmented in order to account for the influence of the electro-mechanical coupling. In this contribution we pursue a comprehensive electro-mechanical characterization of the popular dielectric polymer VHB 4905™. In contrast to the results of the electro-mechanical experiments published previously [2] all of these experiments are conducted without the application of a pre-stretch and are therefore well suited for the identification of the coupling parameters of the material model. The presented model shows excellent agreements with experimental findings.
CRIS-Team Scopus Importer:2019-06-18